The Phenomenon of Natural Resources Exploitation in ‘Mencari Ujung Pelangi': An Ecocritic Approach - Wardani, Yohana Ari (Lakon : Jurnal Kajian Sastra dan Budaya, 2024)
Environmental crisis has become a current issue for literary researches globally including in Indonesia. 'Mencari Ujung Pelangi' through an ecocritical approach, is providing a nuanced backdrop against which to explore the intricate dynamics of natural resource exploitation within literary contexts. This study is using eco-crititicism lens since it focuses on the relationship between literature and the environment. For the purpose of this study, the questions formulated were 1) How does "Mencari Ujung Pelangi" represent nature and environmental issues, and what critique does it offer against anthropocentric attitudes? 2) In what ways does the story promote environmental advocacy and consciousness, and how does it align with the ecocritical goals of fostering ecological awareness? Through the protagonist Alfi's eyes, we witness the impact of deforestation and industrialization”the factory replacing the forest”and the subsequent pollution of the nearby lake. The story critiques anthropocentrism”the human-centric view that prioritizes economic interests over ecological well-being”by highlighting the negative consequences of such attitudes.